2021
DOI: 10.1177/17479541211035556
|View full text |Cite
|
Sign up to set email alerts
|

Coaches’ perceptions of innovation programs of the Royal Spanish Tennis Federation

Abstract: This research studied the coaches’ perceptions of the innovation programs of the Royal Spanish Tennis Federation (RFET) during 2016-2020. The RFET is one of the most relevant national federations in Spain both in terms of results at the highest levels of the game as well as in terms of participation and grassroots tennis. Coaches are considered relevant stakeholders of any sport federation due to their role in delivering the sport. A 29-item questionnaire adapted to tennis was completed by 132 certified coache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(32 citation statements)
references
References 43 publications
4
27
1
Order By: Relevance
“…In terms of innovation, our results are in line with those obtained by previous researchers who investigated coaches’ perceptions of innovative programmes implemented by the RFET and concluded that coaches identified a participation grassroots and a coach education programme as the most relevant of all those implemented. 58 However, the views of the coaches that COVID-19 had negatively affected the innovation strategy and capability of the organization were stronger that those found in this study.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…In terms of innovation, our results are in line with those obtained by previous researchers who investigated coaches’ perceptions of innovative programmes implemented by the RFET and concluded that coaches identified a participation grassroots and a coach education programme as the most relevant of all those implemented. 58 However, the views of the coaches that COVID-19 had negatively affected the innovation strategy and capability of the organization were stronger that those found in this study.…”
Section: Discussioncontrasting
confidence: 73%
“…Furthermore, regarding the innovation programmes identified, our findings coincide with those of previous studies since sport-specific programmes were the most relevant to be delivered by federations or associations. 15 , 30 , 58 , 59 …”
Section: Discussionmentioning
confidence: 99%
“…The Latin American tennis federations provided an interesting view of the challenges these organizations should face and the policies, strategies and programs to fulfill their stakeholders needs (see Crespo et al, 2021c).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…the challenges posed by the pandemic. Different innovative actions that have used digital media, such as online training from home or distance learning, are allowing tennis activity to continue despite the great challenge we face (Crespo et al, 2021).…”
Section: Coaching and Sport Science Reviewmentioning
confidence: 99%
“…
COACHING & SPORT SCIENCE REVIEWthe challenges posed by the pandemic. Different innovative actions that have used digital media, such as online training from home or distance learning, are allowing tennis activity to continue despite the great challenge we face (Crespo et al, 2021).The application of different digital marketing strategies in the field of tennis helps professionals to grow tennis in the context in which they operate, as well as improves their ability to generate business. Therefore, we believe it is crucial for the coach to be able to understand the key trends in the business world in general and in the digital marketing sector that are shaping the socio-economic landscape of tennis.In this context, it can be stated that digital marketing offers a great opportunity for tennis coaches to enhance their professional activity.
STUDIES ON DIGITAL MARKETING AND TENNISStudies on digital marketing and tennis have been varied as they have dealt with areas related to federations, tournaments, and coaches.
…”
mentioning
confidence: 99%